Pengembangan LKPD Berbasis Problem Based Learning Pada Materi Bangun Ruang Kelas V SD - Ulfatul Khoiriah; Jayanti Jayanti; Ida Suryani (Journal on Education, 2023)
This research aims to produce a teaching material product called "Student Worksheets based on Problem Based Learning" that meets the criteria of validity, practicality, and effectiveness. The research utilizes the Research and Development method, employing the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research subjects are fifth-grade students of SD Negeri 12 Sungai Pinang. The research data is obtained from expert validation questionnaires, educator and student response questionnaires, and student learning outcomes. Based on the validation questionnaire results from the expert team, the quality of the media's appearance, language usage, and material presentation received an overall score of 87.60%, indicating a very valid category. The practicality questionnaire, based on the responses of educators and students, obtained an overall score of 91.24%, indicating a highly practical category. The effectiveness questionnaire completed by the students as a whole received a score of 84.76, indicating a highly effective category. Based on the developed results presented in the research titled "Development of Student Worksheets based on Problem Based Learning for Grade V Spatial Concepts in Elementary School," it can be concluded that the Student Worksheets based on Problem Based Learning have been successfully developed and meet the criteria of validity, practicality, and effectiveness